The Role of Pre-recorded Lecture Length and Captioning in Shaping Business Students’ Learning and Engagement (American Journal of Education and Technology, 2025)
Online education has seen substantial growth over the last few years, particularly in the context of the COVID-19 pandemic. The objective of this study was to investigate the impact of pre-recorded lecture duration and the availability of captioning on student engagement and learning effectiveness during the pandemic. Data was collected through a survey of both undergraduate and postgraduate business students at a British university’s partnership campus in Qatar. The results show that students prefer shorter recordings and perceive them as more useful for their learning. Furthermore, students indicated that captions are a very useful addition to pre-recorded video lectures, and that they use both video and captions together to enhance their learning experience. The findings offer valuable insights into the preferences and experiences of students within the context of an online learning environment. Pre-recorded short lectures with captions offer an advantageous learning environment for students, which educators can consider adopting in post-pandemic teaching practices as a more permanent feature.